Developing and evaluating Robocare; an innovative, nurse-led robotic prostatectomy care pathway. (April 2016) - Birch, Emma; van Bruwaene, Siska; Everaerts, Wouter; Schubach, Kathryn; Bush, Matiu; Krishnasamy, Mei; Moon, Daniel A.; Goad, Jeremy; Lawrentschuk, Nathan; Murphy, Declan G.
Abstract: Purpose: A Robotic Prostatectomy Care Pathway ("Robocare"), aiming to prepare men for robotic-assisted radical prostatectomy (RARP) and manage side-effects and long-term follow-up in a multidisciplinary fashion was established. The pathway enhances patient care by providing adequate information and support and optimizes efficiency by reducing length of stay and minimizing hospital visits. Our study assesses the pathway for patient satisfaction, co-ordination of care between disciplines, length of stay and readmission rates. Method: We analysed our database of all patients undergoing RARP with Robocare between July 2012 and December 2013 at Peter MacCallum Cancer Centre, Australia (PMCC). Compliance, Length of Stay and Postoperative Course were analysed. Patient satisfaction was assessed. Results: Overall 124 patients underwent RARP with 105 (85%) being discharged day 1 post-op (mean 1.3 days). Post-operative support phone calls were received by >95% of patients. Thereafter, 74 patients (60%) were followed in the long-term follow-up phone clinic. Twenty-nine complications were identified of which 19 (66%) were resolved by the nurse specialist. Eighteen patients had psychologist, 44 sexual health and 44 physiotherapist referral. Patient satisfaction in 74 (60%) returned surveys revealed 71 (96%) being well/very well supported. Conclusions: The Robocare pathway is safe with high patient satisfaction. It contributes to reducing post-operative length of stay and readmission rates as well as the outpatient follow-up. A true multidisciplinary approach that is nurse-led likely improves care and outcomes for RARP patients and may lower impact on hospital resources. Highlights: We present our nurse-led robotic prostatectomy pathway, suitable for implementation at other hospitals. This pathway is safe, with high patient satisfaction, reduced post-operative length of stay, and readmission rates.